Analysis of the Influence of Auditor Competence, Independence, and Organizational Culture on Audit Quality: A Study of the Supreme Audit Agency (BPK) of West Sulawesi Province - Riana Anggraeny Ridwan; Nurul Listiawati; Nila Adriani (STIE Amkop Makassar, 2026)
Demands for public accountability make audit quality a crucial element for the West Sulawesi Provincial Office of the Supreme Audit Agency of the Republic of Indonesia (BPK RI). This study aims to examine and analyze the influence of auditor competence, auditor independence, and organizational culture—both individually and collectively—on audit quality. Using a quantitative method with a causal design, this study involved 50 auditors as respondents through purposive sampling. Primary data collected via questionnaires were analyzed using multiple linear regression with SPSS software. The results indicate that, individually, competence, independence, and organizational culture have a positive and significant effect on audit quality. Auditor independence was found to be the most dominant variable influencing audit quality. Simultaneously, the three independent variables contributed a very strong 97.2% to the variation in audit quality, as indicated by the Adjusted R² value. Square. These findings confirm that the combination of individual auditors' capabilities and the internalization of organizational values is a key determinant in producing accurate and credible audit reports. Strengthening the aspect of independence is the primary recommendation for maintaining public trust in the transparency of local financial management in West Sulawesi.